SSR and 18S rDNA based molecular profiling of Neopyropia yezoensis (Rhodophyta) in China: insight into genetic impact of laver aquaculture on wild resource - Xu, Hui; Jia, Rujie; Liang, Zhourui; Lu, Xiaoping; Wang, Wenjun (Frontiers in Marine Science, 2023)
Neopyropia yezoensis is a typical intertidal seaweed and an indispensable species for conservation of seaweed resources. As one of the most important marine vegetables, the cultivation area of N. yezoensis has been largely increasing in the past decade and ranked the second highest among all the farmed seaweeds in China. It remains unknown whether large-scale cultivation of N. yezoensis has a genetic impact on wild populations. In this study, SSR markers and 18S rDNA were applied for diversity and genetic structure analysis of 22 N. yezoensis populations from North China. Twenty-two haplotypes were generated from 352 18S rDNA sequences and only three haplotypes were shared by both cultivated and wild populations. Based on 11 polymorphic SSR markers developed, the average polymorphism of the cultivated N. yezoensis populations was higher than that of the wild populations, with the percentage of polymorphic loci being 90.91% in most cultivated populations. The cultivated populations were clustered separately from the wild ones based on the population phylogenetic tree. This indicates that cultivated N. yezoensis populations are diverse and divergent from wild populations in China. However, there were cultivated individuals mixed with the wild ones based on the individual phylogenetic tree and STRUCTURE analysis. The genetic differentiation between cultivated and wild populations decreased with increasing cultivation time, suggesting a possible long-term and slow process of genetic introgression between cultivated N. yezoensis and the wild resource. The wild populations were grouped into two distinct clades by SSRs, with one distributed around the intersection between the Yellow Sea and the Bohai Sea, where the populations were characterized by a specific 18S rDNA haplotype. These findings provide useful insights into germplasm conservation, genetic breeding and improvement of N. yezoensis farming practices.